Back Cover: Synthesis, Characterization, and Metal Ion Coordination of a Multichromophoric Highly Luminescent Polysulfurated Pyrene (Chem. Eur. J. 34/2014). Issue 34 (18th August 2014) - Fermi, Andrea; Ceroni, Paola; Roy, Myriam; Gingras, Marc; Bergamini, Giacomo
<x xml:space="preserve">Abstract</x> Multichromophoric systems capable of operating as light‐harvesting antennae have recently been attracting increasing attention. In their Full Paper on page 10661 ff., M. Gingras, G. Bergamini et al. describe the synthesis, characterization, and metal‐ion coordination of a multichromophoric tetra(terpyridine) ligand that can be used to make new supramolecular systems with tailor‐made photophysical properties and aggregation states.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>